PERANAN PEREMPUAN DALAM MASYARAKAT PERTANIAN DI KABUPATEN TEMANGGUNG (STUDI KASUS PEREMPUAN PETANI TEMBAKAU DI DESA TLAHAP KECAMATAN KLEDUNG) - Arsal, Thriwaty (Faculty of Social Science, Universitas Negeri Semarang, 2009)
This is a qualitative research in the context of role, time allocation, income contribution, and womenÃ‚Â tobacco farmer contribution on decision making. The data source are collected through observation andÃ‚Â in-depth interview with 5 families, including women tobacco farmer, their husbands, and their children,Ã‚Â to fnd the description about women role in public and domestic activities. The research questions are: (1)Ã‚Â what are the roles of women tobacco farmer in Tlahap Village Kledung Subdistrict Temanggung Regency?Ã‚Â (2) how they allocate their time between domestic and public activities? and (3) how is their contributionÃ‚Â in increasing family income? The result of this research shows that the women tobacco farmers haveÃ‚Â high contribution in their family income, around Rp. 2.000.000,00 Ã¢â‚¬â€œ Rp. 3.000.000,00 every harvest,Ã‚Â twice a year. Besides their work as farmer, they have side job that increase their family social economicsÃ‚Â condition. Women tobacco farmer work in farm about 9 hours a day and 5 hours in home, compare withÃ‚Â their husband that only work 9 hours in farm. This fact shows that women tobacco farmer activities areÃ‚Â longer than their husband.Keywords: Women, farm society, tobacco farmer